2022
DOI: 10.1002/ajhb.23829
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of secular trends in physical fitness of children and adolescents (8–18 years) from Kraków (Poland) between 2010 and 2020

Abstract: Objectives The aim of the study was to analyze the changes of the motor skills of children and adolescents from Kraków between 2010 and 2020. Methods The group included 4106 children and adolescents (8–18 years of age). The analysis of changes included results of the following fitness tests: backwards overhead medicine ball throw, standing broad jump, dynamometric strength of the hand, flexibility test, as well as shuttle run (10 × 5 m). Results A negative trend in both sexes was observed in the results of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…On the other hand, for the bent-arm hangs test, we found that most studies showed downward trends, such as in Slovenia 15 , Dutch 43 , Lithuania 39 , and the UK 57 . We also found a decline in backward overhead medicine ball throws in Poland (Krakow) 47 . Kaster et al 19 estimated secular trends of sit-up performance for 9,939,289 children and adolescents aged 9-17 years from 31 countries/regions from 1964 to 2017 and found that most countries showed positive trends.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…On the other hand, for the bent-arm hangs test, we found that most studies showed downward trends, such as in Slovenia 15 , Dutch 43 , Lithuania 39 , and the UK 57 . We also found a decline in backward overhead medicine ball throws in Poland (Krakow) 47 . Kaster et al 19 estimated secular trends of sit-up performance for 9,939,289 children and adolescents aged 9-17 years from 31 countries/regions from 1964 to 2017 and found that most countries showed positive trends.…”
Section: Discussionmentioning
confidence: 61%
“…However, we found that the explosive power of rural boys improved from 2015 to 2018 in Shanghai, China 13 , and improved in Japan in the last decade 36 . Some developed countries, such as Slovenia (until 2014) 21 , Lithuania 39 , Italy 41 , Poland 47 , and Brazil 48 , reported negative trends at the beginning of the twenty-first century or throughout the observed period, with many of these studies showing no significant changes 15,39,41,47 or improvement for girls in recent years 21 . The explosive power of Croatian and German boys had no significant changes and improved for girls slightly since the beginning of the twenty-first century 14,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of these changes showed a clear trend, indicating a systematic improvement in the social and living conditions of society. The biggest change concerned the level of education, self-assessed financial situation, and the number of children in the family [ 32 , 33 , 34 ]. Later, significant economic progress and the following changes in the population’s lifestyle may have strongly influenced the intergenerational increase in trunk circumferences, as well as the values of the derived indicators [ 21 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed, that fitness is a crucial component of overall health (Kryst et al 2022). Thus, children who are unfit are also characterized by an increased risk for cardiovascular and metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%